Adolescent idiopathic scoliosis for the primary care physician: frequently asked questions. Issue 1 (February 2019) - Ghanem, Ismat; Rizkallah, Maroun
Abstract : Purpose of review: Provide primary care physicians with the best available evidence to support answers to frequently asked questions by caregivers of patients with adolescent idiopathic scoliosis (AIS). Recent findings: A review of best available evidence shows that schoolbag design and weight are not associated with higher odds of developing AIS. However, patients with AIS are more prone to balance problems with asymmetric backpack carrying and with rising weights. In patients with AIS, the backpack should be worn in a symmetric way and should never exceed 10% of the child's body weight. Although no relationship was found between systematic exercising in general and development of AIS, classical ballet and professional swimming in skeletally immature adolescents were associated to higher odds of having AIS. Since AIS affects adolescent girls mainly, women health issues are of paramount importance in this disease. Except for limited sexual activity and higher need for infertility treatment, patients with AIS perform similar to controls in marriage rates, age at first pregnancy, gestational age, offspring, labor and delivery. Best available evidence shows that adults with AIS diagnosed during adolescence have similar physical activity level compared with controls. In patients with AIS, adults with surgically treated idiopathic scoliosis have slightly lower physical activity level than previously braced and untreated patients. Summary: Although schoolbag weight isn't associated with higher odds of developing AIS, classical ballet and professional swimming in adolescents are. Except for limited sexual activity, patients with AIS perform similar to controls in remaining women health issues. Adults with AIS diagnosed during adolescence have similar physical activity level compared with controls.